Analisis Tanda Bullying melalui Analisis Tanda Bullying melalui Semiotika Roland Barthes pada Film Imperfect: Analisis Tanda Bullying melalui Semiotika Roland Barthes pada Film Imperfect - Tika, Tika Sagita; Marini (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2025)
This study aims to analyze the representation of bullying in the film Imperfect: Karier, Cinta, dan Timbangan directed by Ernest Prakasa through Roland Barthes’ semiotic approach. This research employs a descriptive qualitative method with data collected through observation and documentation of selected film scenes. The analysis is based on Barthes’ three layers of meaning: denotation, connotation, and myth. The findings reveal that the forms of bullying depicted in the film include verbal, emotional, and symbolic bullying, primarily occurring within family and workplace contexts. The film highlights how beauty standards shaped by popular culture lead to discrimination against women who do not conform to idealized criteria. The myth reflected in the film is the belief that beauty determines one’s value and social acceptance. Through its narrative and visual symbols, the film serves as a social critique of unrealistic beauty constructs and emphasizes the importance of self-acceptance.